A sea of birds: first bird population assessments in the Saudi Arabian Red Sea - Calabrese, Licia; Riordan, Julie Ann; Lloyd, Imogen Anne; Foster, Alexa Darby; Collier, Thomas Edward; Chambon, Johannes Alexandre; Aljohani, Yasir Wusayl; Alhamdi, Essa Ali; Beaumont, Patrick Rowan; Williams, Ivor Douglas; Al-Attas, Omar (Frontiers in Marine Science, 2024)
Seabirds and other insular birds are an important part of the marine ecosystems and increasingly threatened worldwide. Phenology, abundance, distribution and breeding success are important baseline parameters needed to evaluate population trends and dynamics, identify biodiversity hotspots and potential breeding sites, and assess habitat selection.In the Red Sea basin, reliable and complete data on seabirds are lacking for islands in most of the Important Bird Areas (IBA). Such data are now especially important since development projects have started at several of these locations.Here, we assess distribution, abundance, phenology and population trends of 13 seabird species that breed in the Duba islands, Al Wajh Bank and Al Lith islands. Breeding success and habitat selection for six species was also assessed.Between December 2020 and August 2023, more than 90 islands were visited multiple times with different frequency. All nests were counted, and the area occupied by the different colonies georeferenced. Breeding success was assessed by visiting selected colonies multiple times until the chicks were ready to fledge. Habitat selection was determined by analyzing the habitat found in the georeferenced colonies.More than 25,000 nests were counted each year, mainly in summer, on more than 75 islands. Of the 13 species studied, the most abundant and widespread species was the White-cheeked Tern, and the second most widespread was the Osprey.